Endless Run Based Medicinal Plant Educational Game Development - Yazir, M Sofwan; Tosida, Eneng Tita; Karlitasari, Lita (International Journal of Global Operations Research, 2022)
Medicinal plants are very beneficial for health. Medicinal plants can be used as an alternative to cheap and efficient medicine, but not everyone knows what plants can be used as medicine and how to process them. Students are expected to be more familiar with the types of medicinal plants, both local and scientific names, uses, parts used, processing methods, and rules for use. To be able to introduce medicinal plants more interactively, then one solution that can be applied is through application-based games. Educational games are expected to stimulate students to be more active in studying medicinal plants. The game technique used is endless run. Game "Endless Run" is categorized as an action game, has a linear design without ending, without stopping and no stages or changing levels. "Endless Run" is a game where the main character in the game continues to run the game that will not stop. The results of the usability trials shown to teachers, lecturers and students showed good respondents so that people who want to learn the introduction of medicinal plants can obtain information and benefits so that they can increase students' learning desires and the application is easy to operate and the survey results from the percentage (effect 80 %, control 90%, efficiency 70%, helpfulness 80%, learnability 90%). The Endless Run-Based Medicinal Plant Educational Game Development Application can be used by students, college students, millennials and the general public. By utilizing the Unity 3D application, this software includes a game engine capable of handling three-dimensional graphics. This application will run on the Android 8.0 (Oreo) mobile platform with an application capacity of 33.37MB.